Development of acceptance criteria for the results of anti-D IgG quantification in human anti-D (Rhо) immunoglobulin preparations by enzyme immunoassay - E. V. Shvedova; S. A. Leshina; E. Yu. Kudasheva; I. V. Borisevich; V. A. Merkulov; D. V. Shvedov (Биопрепараты: Профилактика, диагностика, лечение, 2022)
The competitive enzyme-linked immunosorbent assay (ELISA) used for the quantification of specific antibodies, anti-D (Rho) IgGs, in human anti-D (Rho) immunoglobulin preparations relies upon the competition between anti-D antibodies in the preparation and anti-D monoclonal antibodies (mAbs) for immunochemical binding to D-antigen epitopes of the immunosorbent, human erythrocytes of the ccDEE phenotype immobilised on a solid support. The immunosorbent is prepared in-house under laboratory conditions. The certification of the International Standard (IS) for anti-D immunoglobulin included attempts to use the CCDee phenotype, which is more common (16.01%) than the ccDEE phenotype (2.16%). It is possible to use the CCDee phenotype, as long as the user adheres to the acceptance criteria for the results, developed during method validation. The aim of this study was to develop the acceptance criteria for the results of anti-D IgG quantification in human anti-D immunoglobulin preparations by the ELISA method that would allow using CCDee erythrocytes to prepare the immunosorbent should there be no erythrocytes of the ccDEE phenotype available. Materials and methods: the study used human anti-D immunoglobulin preparations; anti-D IgG–spiked samples; the IS for  anti-D immunoglobulin; the reference standard (RS) for anti-D IgG–free immunoglobulin; anti-D mAbs; and erythrocytes of the CCDee, ccDEE, and ccddee phenotypes. The authors quantified anti-D IgG antibodies by the competitive ELISA. The statistical analysis used parametric and nonpar ametric tests. Results: the study demonstrated the possibility of using CCDee  erythrocytes for competitive immunochemical binding with anti-D mAbs and anti-D IgG of various human  anti-D immunoglobulin preparations. The suitability of the analytical procedure with the CCDee phenotype was confirmed by validation parameters: trueness, intermediate precision, linearity, selectivity, specificity, and robustness of the method and comparability of the results obtained when using the CCDee and ccDEE phenotypes. The authors developed the acceptance criteria: the relative values of anti-D IgG content in the test sample should range within ±20% of the nominal value; the coefficient of determination (R2) should be at least 0.9; the relative standard deviation (RSD, %) of three absorbance values for each concentration should not exceed 20%. Conclusions: these acceptance criteria guarantee the reliability of assay results of anti-D IgG quantification by the ELISA, which allows them to be used by specialists of control and analytical laboratories to assess the quality of human anti-D immunoglobulin preparations.